PENGHINDARAN PAJAK DI INDONESIA: FAKTOR PROFITABILITAS, INTENSITAS MODAL DAN INTENSITAS PERSEDIAAN : TAX AVOIDANCE IN INDONESIA: PROFITABILITY FACTORS, CAPITAL INTENSITY AND INVENTORY INTENSITY - Rahmawati, Vivi; Indah Hernawati, Retno (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2025)
This research aims to identify the effect of profitability, capital intensity and inventory intensity on tax avoidance in mining companies listed on the Indonesian Stock Exchange from 2019 to 2023. This research is quantitative research using secondary data in the form of company annual financial reports obtained from the official website is www.idx.co.id as well as the official website of each mining company. The analysis technique is multiple linear regression. The population is mining sector companies listed on the IDX in the period 2019 to 2023 and a sample of 112 data was obtained using the purposive sampling. The results show that profitability has influence on tax avoidance, that a greater level of profitability will increase the company's potential to avoid tax.  On the other hand, capital intensity and inventory intensity have no influence on tax avoidance. The companies invest their assets in the fixed assets and inventory are not always used as a reduction in the tax burden but are used as company operational costs.